Żelazne drogi a literatura polskiego romantyzmu - Dziergwa, Roman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The pieces gathered in the new anthology, titled The other road are subversively called by the author; the literature of footnotes and ellipses. It is a new, important and even groundbreaking release for the Polish and socio-anthropological studies as it consists of texts that are regularly omitted in the historical and literary syntheses of Polish romanticism and, as the author rightfully notices, are thus forced to fade into obscurity.
Keywords: koleje; pociągi; dworce kolejowe; rewizja obrazu literatury polskiej; railways; trains; railway stations; Polish literature revision